2019
DOI: 10.1021/acs.jafc.9b00747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imidacloprid Uptake from Contaminated Soils on Vegetable Growth

Abstract: In the present study, the effect of imidacloprid uptake from contaminated soils on the growth of leaf vegetable Shanghaiqing was investigated. The result showed that during 35-day exposure, the concentration of imidacloprid (IMI) was in the order of vegetable shoots > vegetable roots > soil, indicating that IMI was more readily concentrated in vegetable shoots than in roots. Moreover, the biomass of IMI-treated vegetable shoots was comparable to that of the controls with early exposure, but was higher than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 82 publications
(167 reference statements)
0
20
0
Order By: Relevance
“…It is important to note that the subtle (but potentially nutritionally important) disruption of primary metabolism observed in the above studies occurred as a common response to several different pesticides (Mahdavi et al, 2015;Serra et al, 2015;Blondel et al, 2016;Li et al, 2019). This effect appears, thus, not to be linked to particular modes of action by active ingredients.…”
Section: Outstanding Questions and Potential Interactionsmentioning
confidence: 79%
See 2 more Smart Citations
“…It is important to note that the subtle (but potentially nutritionally important) disruption of primary metabolism observed in the above studies occurred as a common response to several different pesticides (Mahdavi et al, 2015;Serra et al, 2015;Blondel et al, 2016;Li et al, 2019). This effect appears, thus, not to be linked to particular modes of action by active ingredients.…”
Section: Outstanding Questions and Potential Interactionsmentioning
confidence: 79%
“…Data from a number of recently published metabolomic studies (see Box 2) indicates that similar biochemical changes (akin to those associated with stress and/or senescence) can occur in crop tissues following exposure to some contemporary pesticide products (Mahdavi et al, 2015;Serra et al, 2015;Blondel et al, 2016;Li et al, 2019).…”
Section: Impacts Of Pesticide Exposure On Crops' Susceptibility To Pandpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinic acid and oxalic acid are considered to be the main C sources of denitrification microorganisms ( Liu et al, 2016 ), and some phenolic substances have been shown to promote organic matter in soil decomposition by stimulating changes in microbial community composition ( Huang et al, 2019 ). Plant roots can release amino acids and exert a variety of biological effects by passive diffusion; for example, the osmotic adjustment substance proline can protect cell membranes from oxidative stresses and stabilize protein structure ( Li et al, 2019 ). In addition, some substances such as benzoic acid, hydrocarbons, and others detected were allelopathic substances, which could affect seed germination and microbial growth and possibly interfere with the growth of other plants.…”
Section: Discussionmentioning
confidence: 99%
“…Imidacloprid (IMI), the first‐generation neonicotinoid insecticide, was introduced in 1991 and applied in aquaculture systems, leading to much residues in water [1]. Residues of IMI can even exist for months or years because of its high persistence in environment [2]. So far, IMI has been detected in groundwater or aquatic systems in many countries and regions, such as united states, brazil, china and so on [3].…”
Section: Introductionmentioning
confidence: 99%